Frailty and oral health-related quality of life in community-dwelling older adults: a cross-sectional study - Roosevelt Silva BASTOS; Leticia Marques SÁ; Sofia Rafaela Maito VELASCO; Debora Foger TEIXEIRA; Larissa Sanches PAINO; Mario Vianna VETTORE (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract Poor oral health has been associated with frailty among older adults. However, limited evidence has been available on whether frailty can affect oral health-related quality of life (OHRQoL) in older adults. This study aimed to investigate the relationship between frailty and OHRQoL among community-dwelling older adults. A household-based cross-sectional study involving community-dwelling older adults aged 65 years and older was conducted in the city of Bauru, Brazil. Data on frailty status, sociodemographic characteristics, self-perceived dental care needs, and OHRQoL (OHIP-14) were collected through individual interviews. The use of and the need for total dental prostheses were assessed through clinical examinations. Logistic regression was used to determine whether frailty status and covariates were associated with OHRQoL prevalence measures (OHIP-14 total score ≥ 1 and OHIP-14 fairly/very often ≥ 1). The sample comprised 334 participants, among whom 58.7% and 41.3% were between 65-74 and 75-102 years old, respectively. The prevalence of moderate to severe frailty was 12.3%. Moderate to severe frailty (OR = 4.49; 95%CI 1.29-15.66), the need for lower dental prosthesis (OR = 2.20; 95%CI 1.27-3.81), and self-perceived dental care need (OR = 3.90; 95%CI 2.14-7.14) were associated with OHIP-14 total score ≥1. Moderate to severe frailty (OR = 2.95; 95%CI 1.33-6.55), being female (OR = 2.24; 95%CI 1.34-3.75), and self-perceived dental care need (OR = 4.80; 95%CI 2.86-8.03) were associated with OHIP-14 fairly/very often ≥1. Overall, our results showed that moderate to severe frailty was significantly associated with poor OHRQoL in community-dwelling older adults.